PELAYANAN PRIMA DI KANTOR IMIGRASI KLAS I KOTA TANJUNGPINANG - Samin, Rumzi; Panjaitan, Ronny Dwi Saputra (Jurnal Ilmu Administrasi Negara (JUAN), 2016)
PELAYANAN PRIMA DI KANTOR IMIGRASI KLAS I KOTATANJUNGPINANG Ronny Dwi Saputra Panjaitan Rumzi Samin (rumzi@hotmail.co.id) (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract: Service is the process of fulfilling the needs of what is required of others. In general, the service can be interpreted by doing that the results intended for the benefit of others, whether individuals, groups, or communities. Excellent service is very good service or services that best meet customer needs. Thus the Immigration Office Class I Tanjungpinang required to perform excellent service. The purpose of this study was to determine the excellent service given Class I Immigration Office Tanjungpinang. This research is a descriptive study using quantitative methods. The data collection in this study is through observation and questionnaires. Data analysis techniques used in this research is to calculate the degree of correspondence between expectations and reality as well as by measuring the index numbers. The data were processed using the formula degree of suitability and importance of decision making using performance analysis, the index number obtained by calculating the weight and frequency and decision-making through the established criteria. Informants / respondents in this study obtained through the use of techniques that is incidental sampling technique of determining based on chance. The population in this study are all the people who do the maintenance at the Immigration Office Class I Tanjungpinang. Questionnaires were distributed to 50 respondents. Research results obtained from processing the data as a whole and is shown by the percentage figure of 59.8%. Much to be improved in order to create excellent service or services that best meet the public expectation to the Immigration Office Class I Tanjungpinang, especially on the reliability indicator (reability), responsiveness (responsiveness), and attention (empathy). The general conclusion of the study at the Immigration Service Excellence Class I Tanjungpinang is a prime service can not be said because it still can not give what is expected or desired community / customers. Suggestion of this research is the Immigration Office Class I Tanjungpinang should further improve overall service to achieve the best service or excellent service. When reached or the realization of excellent service in Class I Immigration Office Tanjungpinang will certainly have a positive impact for the office itself.